2014
DOI: 10.1021/jm401349g
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species (ROS) Inducible DNA Cross-Linking Agents and Their Effect on Cancer Cells and Normal Lymphocytes

Abstract: Reducing host toxicity is one of the main challenges of cancer chemotherapy. Many tumor cells contain high levels of ROS that make them distinctively different from normal cells. We report a series of ROS-activated aromatic nitrogen mustards that selectively kill chronic lymphocytic leukemia (CLL) over normal lymphocytes. These agents showed powerful DNA cross-linking abilities when coupled with H2O2, one of the most common ROS in cancer cells, whereas little DNA cross-linking was detected without H2O2. Consis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
92
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 47 publications
2
92
0
1
Order By: Relevance
“…Evidence has shown that the expression of HO-1 was increased by HIF-1α (12,13). Moreover, oxidation stress exists in tumors (14). Additionally, we found that HO-1 is positively correlated with HIF-1α.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Evidence has shown that the expression of HO-1 was increased by HIF-1α (12,13). Moreover, oxidation stress exists in tumors (14). Additionally, we found that HO-1 is positively correlated with HIF-1α.…”
Section: Discussionsupporting
confidence: 63%
“…Various ROS are always found in normally functioning cells and are thought to be a normal part of cell growth, proliferation and differentiation. ROS are usually found in very high levels in tumor cells (14). These high intracellular levels could affect normal cellular function and may contribute to tumor progression (17,18) We hypothesized that the decrease in HO-1 expression and ROS levels may affect the expression of apoptosis-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Very recently, our group discovered that photoirradiation of several phenyl boronates efficiently produced bifunctional benzyl cations cross-linking DNA at dG and dC sites.…”
mentioning
confidence: 99%
“…18 However, to date, most of the reported charge reversal of nano-drug carriers depend on the change of pH profile of cancer cells . [16][17][18] It is well know that cancer cells also produce high amounts of superoxide, [19][20][21] hydrogen peroxide, 22-24 hydroxyl radicals 25 and hydrogen sulfide. 26 .…”
Section: Introductionmentioning
confidence: 99%